PERENCANAAN PEMBANGUNAN DI DESA GAMSIDA KECAMATAN IBU SELATAN KABUPATEN HALMAHERA BARAT - BUSELA, ARBID; POSUMAH, JOHNNY HANNY; TAMPI, GUSTAAF BUDDY (Sam Ratulangi University, 2020)
Based on the background of the problem, the Government is still inadequate in empowering the communityto increase plantation yields, so this research aims are: to determine development planning in GamsidaVillage, Ibu Selatan District, West Halmahera RegencyIn this research, the writer uses descriptive type which aims to describe and carefully the phenomenon orsocial reality by describing or describing the problem being studied qualitatively. To obtain information inaccordance with the problems under study about how development planning in the village, then usetechniques in an effort to collect data, namely through interviews, observation and documentationThe results show that development planning is a very important process in the implementation ofdevelopment, one of the keys to the success of development objectives is the extent to which developmentplanning is carried out. Village Development is also an effort to improve the quality of life and life as muchas possible for the welfare of the Village community.Keywords: Planning, Development, Village